Psikolojik Sözleşme İhlalinin İş Performansına Etkisi: Duygusal Bağlılığın Aracılık Rolü - Acaray, Ali (Muş Alparslan Üniversitesi, 2019)
The purpose of this study is to investigate the effect of psychologicalcontract breach on job performance and the mediating role of affectivecommitment on this effect. The survey technique was used to collect the dataand 227 samples working full-time in banks were reached with the conveniencesampling method. Job performance was examined as task performance and employeevoice. Research results showed that psychological contract breach had a negativeeffect on task performance and employee voice. Affective commitment had a fullymediating role on the effect of psychological contract breach on taskperformance. Affective commitment had a partly mediating role on the effect ofpsychological contract breach on employee voice. Furthermore, psychologicalcontract breach negatively affected employee voice more than task performance.

Buçalışmanın amacı, psikolojik sözleşme ihlalinin iş performansına etkisini ve buetkide duygusal bağlılığın aracılık rolünü incelemektir. Çalışma verilerinintoplanmasında anket tekniği kullanılmış olup kolayda örnekleme yöntemiylebankalarda tam zamanlı biçimde çalışan 227 örneklem sayısına ulaşılmıştır. İşperformansı; görev performansı ve işgören sesliliği olarak incelenmiştir.Çalışma sonucunda ulaşılan bulgulara göre; psikolojik sözleşme ihlali görevperformansı ve işgören sesliliğini olumsuz olarak etkilemiştir. Duygusalbağlılık değişkeninin de psikolojik sözleşme ihlalinin görev performansınaetkisinde tam, işgören sesliliğine etkisinde ise kısmi aracılık rolü ortayaçıkmıştır. Ayrıca psikolojik sözleşme ihlali, çalışanların işgörensesliliklerini görev performansına göre daha fazla olumsuz olarak etkilemiştir.
The Effect of Psychological Contract Breach on Job Performance: the Mediating Role of Affective Commitment
anemon
Keywords: Psychological Contract Breach; Affective Commitment; Task Performance; Employee Voice; Psikolojik Sözleşme İhlali; Duygusal Bağlılık; Görev Performansı; İşgören Sesliliği